Poverty and Food Security in Brazil during the Pandemic - World Bank (Washington, DC, 2022)
In contrast with the rest of Latin America and the Caribbean, Brazil’s poverty rate is estimated to have decreased between 2019 and 2020 to 13.1 percent. Auxílio Emergencial (AE), a large emergency cash transfer program launched in April 2020, is believed to be the main driver of that decrease, because it more than offset economic losses caused by the COVID-19 pandemic. Nonetheless, food insecurity (FI) estimates showed an opposite trend: Severe and moderate FI went up in 2020. This apparent paradox can be mostly explained by the way in which poverty and FI are measured: Measurements of poverty are based on annualized income estimates, while those of FI are based on the occurrence of an event, whereby the sudden, uncompensated loss of a job or reduction of benefits (such as AE) can turn into the loss of a household’s ability to feed itself in the short term. In 2021, both poverty and FI may have increased. Simulations suggest that poverty increased in 2021 to 18.7 percent. Meanwhile, about 18 percent of households reported running out of food in the past 30 days owing to a lack of resources, twice the pre-pandemic rate. Overall and food inflation, a sluggish labor market recovery with falling real wages, and the significant scaling down of the AE program are all factors in this trend. The war in Ukraine has pushed inflationary expectations upward. Given the projected 0.7 percent gross domestic product (GDP) growth for 2022, labor incomes are not expected to boost households’ consumption levels significantly. Coupled with the complete elimination of AE, poverty and FI may further deteriorate in 2022.